Collected tsetse tissue and tsetse species (Glossina sp.) collected in protected and tsetse invested areas in Nigeria - Weber, Judith Sophie; Shaida, Stephen Saikiu; Ngomtcho, Sen Claudine Henriette; Musa, Usman Baba; Adamu, Ahmadu; Gbem, Thaddeus Terlumun; Berger, Petra; Mamman, Mohammed; Nok, Jonathan Andrew; Kelm, Sørge (In: Weber, JS et al. (2020): Molecular and morphological characterization of Glossina sp. and identification of associated Trypanosoma sp. in Nigeria including analysis for sialidase activity [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.915145, 2020)
This data set includes data from a tsetse (Glossina sp.) collection carried out in Nigeria between 2014 and 2016. Traps were employed for one to three days in four different National Parks, one Game Reserve and two tsetse invested areas. Each tsetse was identified morphologically and dissected in the field. Wings were removed and stored dry. Legs were immersed in a DNA-preservation agent. Salivary glands and ovaries were dissected and stored in a DNA-preservation agent. The whole gut was dissected, homogenized in the field and partially preserved for DNA analysis and used to investigate for sialidase activity. The data table summarizes the available tissue, sex and species information for each dissected specimen. Species collected were G. morsitans submorsitans, G. tachinoides, G. palpalis palpalis and several unidentified Glossina species.